Keeping Communities Healthy: The Islamic Paradigm - Nordin, Musa Mohd (International Journal of Human and Health Sciences (IJHHS), 2018)
One of the five matters before being overtaken by its opposite as advocated by the Prophet (SAW) was “your health, before you fall sick” (Muslim). This concept of the Prophet’s Medicine (Tibb Nabawi) has been much discussed and unfortunately misunderstood, even abused in recent times. This paper attempts to examine the Quranic exhortations on health and healing and its practices as exemplified by authentic traditions of the Prophet (SAW). This would enable us to extract guiding principles about various healthcare issues including holistic care, preventative strategies, training, bioethics, hospital services, clinical research and global health. International Journal of Human and Health Sciences Vol. 02 No. 02 April’18. Page : 49-54